Squamous cell carcinoma in a kidney transplant recipient after 26 years - Carolina da Silva Nunes; Andreia Bufalino; Cláudia Maria Navarro; Jorge Esquiche León; Héric de Souza Camargo; Elaine Maria Sgavioli Massucato (Oral Oncology Reports)
Kidney transplantation is the preferred treatment for patients with end-stage renal disease. However, the immunosuppressive therapy used to prevent graft loss can lead to various complications, including cancer, which is the most severe. This paper reports a clinical case of squamous cell carcinoma that developed in the oral cavity of a kidney transplant patient who underwent the procedure 26 years ago and did not present classic risk factors, such as smoking and alcohol consumption, for the development of the lesion. The lesion on the gingival ridge was reddish in color, had a granulomatous surface, and was firm on palpation. It extended from the lower left incisors to the molars. Additionally, there was an increase in lymph nodes in the ipsilateral submandibular region. According to the literature, malignant neoplasms can take an average of 20 years to develop after transplantation, with the risk increasing considerably to over 45%. The oral cavity is a predilection site in the head and neck region, and many lesions are associated with human papillomavirus (HPV), an oncogenic virus whose infection can be potentiated by chronic immunosuppression in transplant patients. In addition, some drugs, regardless of their immunosuppressive mechanisms, have the ability to induce carcinogenesis, with cyclosporine and azathioprine being clear examples. Therefore, we must always pay attention to this group of patients because we know that they are more susceptible to oral cancer, even in the absence of classic risk factors.